2018
DOI: 10.1155/2018/8457012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Methicillin-Resistant Staphylococci Clinical Isolates from a Tertiary Hospital in Northern Thailand

Abstract: Methicillin-resistant staphylococci are now recognized as a major cause of infectious diseases, particularly in hospitals. Molecular epidemiology is important for prevention and control of infection, but little information is available regarding staphylococcal infections in Northern Thailand. In the present study, we examined antimicrobial susceptibility patterns, detection of antimicrobial resistance genes, and SCCmec types of methicillin-resistant S. aureus (MRSA) and methicillin-resistant coagulase-negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
13
1
Order By: Relevance
“…The MRS prevalence reported in our study is consistent with studies from Cameroon where 72 and 75% of MRS were detected in clinical [3] and carriage [1] samples in Yaounde, respectively. In contrast, the results are lower than that reported from a survey conducted in a tertiary hospital in Northern Thailand where a maximum prevalence of MRS (100%) was detected from clinical isolates [8]. These results are however, higher in comparison with that reported in studies from other part of the world.…”
Section: Discussioncontrasting
confidence: 88%
“…The MRS prevalence reported in our study is consistent with studies from Cameroon where 72 and 75% of MRS were detected in clinical [3] and carriage [1] samples in Yaounde, respectively. In contrast, the results are lower than that reported from a survey conducted in a tertiary hospital in Northern Thailand where a maximum prevalence of MRS (100%) was detected from clinical isolates [8]. These results are however, higher in comparison with that reported in studies from other part of the world.…”
Section: Discussioncontrasting
confidence: 88%
“…In terms of antimicrobial susceptibility, similar results have been reported in other studies. For instance, in a series of MRSA strains isolated from different samples, Kitti et al [14] found high levels of resistance to ciprofloxacin (72.1%), erythromycin (86.9%), gentamicin (72.1%), and clindamycin (86.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Multilocus sequence typing (MLST) analysis of S. aureus is important for the prognosis of infection, and it provides means to trace epidemiologically related strains contributing to the tracking of the contamination source. The MLST types of S. aureus vary with regions and sources ( Pereira et al, 2009 ; Cheng et al, 2013 ; Rao et al, 2015 ; Thapaliya et al, 2017 ; Htun et al, 2018 ; Kitti et al, 2018 ; Wu et al, 2018 ; Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%